The Effects of Social Media Call-Out Culture and Digital CSR Communication on Green Brand Equity and The Role of Perceived Digital Accountability as An Intervening Variable (A Study of Eiger Indonesia Consumers) - Noorieta, Aqsha; Erpurini, Wala (International Journal of Management Science and Information Technology, 2026)
This empirical study examines how a Culture of Criticism on social media and Digital CSR Communications shape Eco-Friendly Brand Equity, highlighting the mediating mechanism of Perceived Digital Accountability among Eiger Indonesia consumers. Amid growing consumer skepticism toward corporate greenwashing practices, outdoor gear brands face dual pressure from public criticism online and their own proactive sustainability messaging. Using a quantitative cross-sectional design, empirical data were collected via an online survey targeting 143 active followers of the @eigeradventure Instagram account aged 18 to 45, selected through purposive sampling. Statistical analysis was conducted using Multiple Linear Regression along with the Sobel Test and the SPSS PROCESS Macro to test both direct pathways and indirect structural relationships. The structural framework indicates that the Culture of Accountability on social media and Digital CSR Communication significantly drive Perceptions of Digital Accountability, which in turn serve as a crucial determinant of Eco-Friendly Brand Equity. Furthermore, Perceived Digital Accountability serves as an essential psychological bridge that transforms external public scrutiny and corporate sustainability signals into enhanced brand trust, an eco-friendly image, and customer satisfaction. Based on Signaling Theory, this study contributes to contemporary brand management literature by emphasizing digital accountability as a vital strategic pillar and providing practical guidance for outdoor brand managers in navigating digital public scrutiny.
Keywords: Critical Culture on social media; Digital CSR Communication; Perceptions of Digital Accountability; Eco-Friendly Brand Equity; Eiger Indonesia